2016
DOI: 10.1007/s10552-016-0839-x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is an independent risk factor for colonic adenomatous neoplasms

Abstract: Helicobacter pylori infection is an independent risk factor for colonic adenomas, especially in cases of advanced or multiple adenomas, but not for rectal adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…In a Korean study on 4,466 subjects who underwent screening colonoscopy and esophagogastroduodenoscopy (EGD), H. pylori infection was associated with a twofold increase in the risk of advanced colon adenomas and multiple colon adenomas. 20 Similar data were reported in a retrospective cross-sectional study on 6,351 Korean subjects (mean age 51.7±8.1 years) who had a GI endoscopy for screening purposes. 21 In this study, Lee et al Previous studies, however, showed that the observed relationship between H. pylori and CRC could be population related.…”
Section: H Pylori and Colorectal Cancersupporting
confidence: 83%
See 1 more Smart Citation
“…In a Korean study on 4,466 subjects who underwent screening colonoscopy and esophagogastroduodenoscopy (EGD), H. pylori infection was associated with a twofold increase in the risk of advanced colon adenomas and multiple colon adenomas. 20 Similar data were reported in a retrospective cross-sectional study on 6,351 Korean subjects (mean age 51.7±8.1 years) who had a GI endoscopy for screening purposes. 21 In this study, Lee et al Previous studies, however, showed that the observed relationship between H. pylori and CRC could be population related.…”
Section: H Pylori and Colorectal Cancersupporting
confidence: 83%
“…Colorectal cancer (CRC) has been confirmed to be positively associated with H. pylori . In a Korean study on 4,466 subjects who underwent screening colonoscopy and esophagogastroduodenoscopy (EGD), H. pylori infection was associated with a twofold increase in the risk of advanced colon adenomas and multiple colon adenomas …”
Section: H Pylori and Colorectal Cancermentioning
confidence: 99%
“…The association between H. pylori infection and CRC is still controversial with studies showing a close link with a higher prevalence of H. pylori infection in patients with colonic adenomas and carcinomas [169,170,171,172], while others do not [173,174,175]. Recent studies released in 2017 have suggested indeed a significant association between H. pylori infection and an increase in CRC occurrence [176,177,178]. Yan and colleagues showed a positive association between H. pylori and CRC only when H. pylori is associated with intestinal metaplasia [178].…”
Section: Possible Mechanisms Of Action Of the Intestinal Microbiotmentioning
confidence: 99%
“…Yan and colleagues showed a positive association between H. pylori and CRC only when H. pylori is associated with intestinal metaplasia [178]. Analyzing 1245 colorectal adenomas and 3221 control subjects without polyp, Nam and colleagues showed that the overall rate of positive H. pylori infection is increased in adenoma cases compared to polyp-free control cases, and that the positive association of H. pylori infection with colorectal adenomas is more prominent in advanced adenomas and multiple adenomas [177]. Despite this controversy, some studies have tried to clarify the mechanism underlying the potential association between this pathogen and CRC with some hypotheses including release of toxin or hormone, intestinal microbiota fluctuation and chronic inflammation.…”
Section: Possible Mechanisms Of Action Of the Intestinal Microbiotmentioning
confidence: 99%
“…(8,9) Moreover, several investigations have reported an association between H. pylori infection and colorectal neoplasms. (10)(11)(12)(13) In general, risk of colorectal neoplasms increases because of some risk factors, such as lifestyle characteristics, anthropometric parameters, and metabolic syndrome. (14,15) Most colorectal neoplasms found during endoscopic examinations are adenomas that possess the potential for cancer in the adenomacarcinoma sequences.…”
mentioning
confidence: 99%